The Influence of Transformational Leadership and Compensation on Teacher Performance through Organizational Commitment in Islamic Fondation - Djoko Soelistya (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
Education determines a country's development and standard of living. The nation's quality is impacted by the quality of education. Good education is common in developed countries. Good instructors are the source of a good education. Performance of teachers has a significant impact on student achievement in education. This research sought to ascertain the impact of transformational leadership and compensation on teacher performance at the Islamic Foundation for Education Malik Ibrahim Gresik via organisational commitment. A quantitative explanatory technique is used in this study. The following inferences may be made in light of the analysis's findings: Teacher performance is directly impacted by two factors: (1) transformational leadership; and (2) compensation. (3) Organisational commitment is directly impacted by transformational leadership. (4) Organisational commitment is directly impacted by compensation. (5) The performance of teachers is directly impacted by organisational commitment. (6) Transformational Leadership has a direct impact on teacher performance rather than acting as a mediator via organisational commitment. (7) Organisational commitment acts as a mediating factor between compensation and teacher effectiveness.